Improving Marketing Approaches to the Energy Sector of Kazakhstan for Decarbonization - Aizhana, Maldynova; Maira, Davletova; Assel, Ilyas; Erkebulan, Butin (International Journal of Energy Economics and Policy, 2022)
This article is devoted to the study of marketing approaches to decarbonization to the energy sector of Kazakhstan. Obviously, it is important for Kazakhstan, with its economy based on the export of raw materials, to boost the use of technologies and approaches for decarbonization already now. These include technologies for carbon capture and storage, energy conservation, as well as the transfer of electricity generation to renewable sources and the use of offset mechanisms. The authors substantiated the need for the formation of a marketing strategy at the enterprises of the energy market of Kazakhstan to promote the ideas of decarbonization, green economy and ecology. Most of The Group of Twenty countries have set ambitious climate change targets that must be translated into clear strategic actions to bring about the needed change. Achieving carbon neutrality requires collaboration across sectors. Implementing climate change action on the scale needed requires marketing approaches that incentivize action on climate change. Servitization is not just a service offering, but a fundamental organizational and cultural change in an enterprise. The purpose of the research is to form a marketing approach of servitization for decarbonization. The SPSS software was used to test the hypotheses put forward in the article. The results of the research can be used to develop and implement strategies for the servitization of a energy market. Companies need to carry out motivational transformations related to the need to introduce servitization.